The fool and the heretic : how two scientists moved beyond labels to a Christian dialogue about creation and evolution /: how two scientists moved beyond labels to a Christian dialogue about creation and evolution. (2019) - Wood, Todd Charles; Falk, Darrel R, 1946-
No abstract available